MSP-RON Signaling Is Activated in the Transition From Pancreatic Intraepithelial Neoplasia (PanIN) to Pancreatic Ductal Adenocarcinoma (PDAC) - Li, Ce; Morvaridi, Susan; Lam, Gloria; Chheda, Chintan; Kamata, Yoshiko; Katsumata, Makoto; Edderkaoui, Mouad; Yuan, Xiaopu; Nissen, Nicholas; Pandol, Stephen J.; Wang, Qiang (Frontiers in Physiology, 2019)
Pancreatic ductal adenocarcinoma (PDAC) is among the deadliest epithelial malignancies and remains difficult to treat. Pancreatic intraepithelial neoplasias (PanINs) represent the majority of the pre-cancer lesions in the pancreas. The PDAC microenvironment consists of activated pancreatic stellate cells and immune cells, which are thought to contribute to neoplastic transformation. However, the signaling events involved in driving the transition from the neoplastic precursor to the more advanced and aggressive forms in the pancreas are not well understood. Recepteur d'Origine Nantais (RON) is a c-MET family receptor tyrosine kinase that is implicated in playing a role in cell proliferation, migration and other aspects of tumorigenesis. Macrophage stimulating protein (MSP) is the ligand for RON and becomes activated upon proteolytic cleavage by matriptase (also known as ST14), a type II transmembrane serine protease. In the current study, by immunohistochemistry analysis of human pancreatic tissues, we found that the expression levels MSP and matriptase are drastically increased in during the transition from the preneoplastic PanIN stages to the more advanced and aggressive PDAC. Moreover, we show that RON is highly expressed in both PDAC and in cancer-associated stellate cells. In contrast, MSP, RON and matriptase are expressed at low levels, if any, in normal pancreas. Our study underscores an emerging role of MSP-RON autocrine and paracrine signaling events in driving malignant progression in the pancreas.